在英語教學法課學習設計和教授差異化教學 Learning to Plan and Teach Differentiated Instruction in a TESOL Methods Course - 簡靜雯 Chin-Wen Chien (National Changhua University of Education, 2015)
本個案研究探討差異化課程融入臺灣語言師資培育課程英語教學法課程內，分析四十六位大學生教案設計和在小學的課程實踐。研究參與者建構差異化課程經歷四個階段，從對差異化課程完全沒有概念到能夠在小學英語課程內實施層級學習單。研究結論認為：差異化課程知識的重要性以及授課者在小學學生進行差異化教學的演 示，應該融入語言師資培育課程中。 This case study discusses the integration of differentiated instruction into a TESOL Methods course in a language teacher education program in northwest Taiwan. Forty-six undergraduate students' lesson plan designs and teaching practices in elementary schools were analyzed. Participants constructed knowledge and skills about differentiated instruction through four stages, from having no idea about differentiated instruction to being able to implement tiered worksheets in elementary school English classes. Results indicate that the importance and knowledge base of differentiated instruction as well as the instructor's real demonstration of differentiated instruction among elementary school students should be included in language teacher education programs.